2012
DOI: 10.1002/anie.201108181
|View full text |Cite
|
Sign up to set email alerts
|

Fast, Cell‐Compatible Click Chemistry with Copper‐Chelating Azides for Biomolecular Labeling

Abstract: We report that azides capable of copper-chelation undergo much faster “Click chemistry” (copper-accelerated azide-alkyne cycloaddition, or CuAAC) than nonchelating azides under a variety of biocompatible conditions. This kinetic enhancement allowed us to perform site-specific protein labeling on the surface of living cells with only 10–40 µM CuI/II and much higher signal than could be obtained using the best previously-reported live-cell compatible CuAAC labeling conditions. Detection sensitivity was also incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
266
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 303 publications
(273 citation statements)
references
References 27 publications
4
266
0
3
Order By: Relevance
“…This showed that the triazoles linker between rGO and AuNPs were very efficient for charge separation and electron transfer [203]. In the field of biology, click chemistry has also been extensively used with various successful biological, chemical and medicinal applications [204] including nucleic acid ligation [205], bioconjugation for protein modification [206], drug design [207], gel syntheses for biomedical applications [208], chemical modification of biological molecules [209], and biomolecular labeling [210] activity-based protein profiling (ABPP) [211].…”
Section: Applications Of the Cuaac "Click" Reactionsmentioning
confidence: 99%
“…This showed that the triazoles linker between rGO and AuNPs were very efficient for charge separation and electron transfer [203]. In the field of biology, click chemistry has also been extensively used with various successful biological, chemical and medicinal applications [204] including nucleic acid ligation [205], bioconjugation for protein modification [206], drug design [207], gel syntheses for biomedical applications [208], chemical modification of biological molecules [209], and biomolecular labeling [210] activity-based protein profiling (ABPP) [211].…”
Section: Applications Of the Cuaac "Click" Reactionsmentioning
confidence: 99%
“…This chemical transformation is characterized by high chemoselectivity and broad tolerance to diverse reaction condition and functional groups. 23,24,[126][127][128][129] In addition, as neither azide nor alkyne is generally present in biomolecules, they are bioorthogonal functional groups.…”
Section: Cell Surface Bioconjugationmentioning
confidence: 99%
“…135,[137][138][139] In order to facilitate this CuAAC reaction for biomolecules chelating ligands were developed to stabilize the Cu(I)-ion (Figure 8). [127][128][129][140][141][142][143][144][145][146][147] The application of these Cu(I)-ligands decreased the effective concentration of reducing agent and copper-salts, and also accelerated the bioconjugation reaction and protected the biomolecules from the oxidation by ROS. 127,129,[148][149][150] Aminoguanidine, a carbonyl-capturing reagent is frequently used because it stabilizes proteins during CuAAC by avoiding the adverse effects of ascorbate and its byproducts.…”
mentioning
confidence: 99%
See 2 more Smart Citations